La territorialisation de la transition énergétique : les paradoxes de la surenchère des normes et de la réglementation - Hélène Nessi (Territoire en Mouvement)
The rapid changes in energy transition objectives imposed at the European level over the last six years and the centralizing position of the French state imply several types of contradictions in the implementation of these objectives. This article examines the consequences of the dynamics of change driven by state actors, particularly in terms of territorial strategy, standards and financial incentives, on the construction of a local energy transition policy and the implementation of the energy transition. The State's implementation of these objectives on several territorial scales is achieved through two public action components: top-down climate-air-energy planning and thermal regulation of buildings. While the observation of numerous dissents and discrepancies proves that energy territorialization is underway, it also shows the difficulties in achieving top-down objectives. The State's stranglehold on energy regulation, financial support, and laws on self-consumption make it difficult to build a real local energy transition policy that is more or less independent of the State's pro-nuclear and highly technical vision. The energy issue is finally reflected more in urban policies, particularly in the production of new housing, which is subject to both local energy policies and sometimes dissonant thermal regulations.